Ku band RF front end receiver of a mobile terminal for satellite communication and IoT solutions - Andrade, Guilherme Felix de (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.